Pengelolaan Keuangan Rumah Tangga Untuk Mencapai Keluarga Sejahtera Di Desa Pagerageung Kp. Pagerageung Tengah - Fitriani Fitriani; Agoes Hari Edy Wibowo; Iqbal Khoirul Mizan (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
This community service program aims to enhance the knowledge and skills of the community in managing household finances as an effort to achieve family welfare. The activity was conducted in Pagerageung Village, Pagerageung Tengah, targeting housewives and local residents. The methods employed included socialization, training, simulation, and mentoring in preparing household budgets and financial records. The results of the program indicate a significant improvement in participants’ financial literacy and financial management behavior. Based on the evaluation of 30 participants, financial literacy increased from 46.7% to 86.7%, budgeting skills improved from 30% to 80%, financial recording habits rose from 26.7% to 70%, and saving awareness increased from 50% to 90%. These findings suggest that a combination of theoretical and practical approaches in training is effective in improving participants’ financial management capabilities. Furthermore, the program contributed to positive behavioral changes in managing finances in a more structured, efficient, and future-oriented manner. Therefore, this community service activity provides a meaningful contribution to improving family welfare through strengthening financial literacy in the community.